Smell and taste abnormalities: early clinical biomarkers for isolating the positive cases in COVID-19 pandemic - Swain, Santosh Kumar (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Coronavirus disease 2019 (COVID-19) is an infectious disease of the respiratory tract caused by a novel virus called severe acute respiratory syndrome corona virus 2 (SARS-Co-2). It primarily spread human to human by droplets which carry virus. The common clinical presentations of the COVID-19 patients are fever, cough, fatigue, gastrointestinal symptoms and dyspnea. Smell and taste abnormalities have recently documented among patient with COVID-19 infection which hypothesize that olfactory mucosa and oral cavity mucosal lining possess SARS-CoV-2 virus. Some COVID-19 patients are also presenting with isolated smell and taste disturbances even without any other respiratory symptoms. Currently there is no effective treatment available for COVID-19 infections. So screening, early diagnosis and isolations are essential in this pandemic. Identifying the early symptoms in COVID-19 patient is priority now in health care system. In COVID-19 pandemic, patient presenting with loss of smell and taste should initiate home isolation and social distancing for avoiding further spread of this disease. This can be confirmed by diagnostic test such as reverse transcriptase-polymerase chain reaction (RT-PCR) when available. Sudden onset of smell/olfactory and taste/gustatory dysfunctions should be considered in routine work up and screening of the patients with COVID-19 infection. This review article focuses on the smell and taste abnormalities among COVID-19 patient which will surely increase the awareness among the front liner clinicians and help them for early diagnosis of the patient and their management.